An Investigation of the Role of Macular Pigment in Attenuating Photostress through Comparison between Blue and Green Photostress Recovery Times. (3rd April 2019) - Tavazzi, Silvia; Perego, Filippo; Ferraro, Lorenzo; Acciarri, Maurizio; Zeri, Fabrizio
ABSTRACT: Purpose : Photostress recovery time (PSRT) is the time required for the macula to return to its normal functioning after the bleaching of cone photopigments due to light exposure, usually white. This work investigates the role of macular pigment (MP) as an optical filter that attenuates photostress by analyses of PSRT at different wavelengths. Methods : Thirty-nine subjects (19–28 years) were exposed to blue/green photostress varying in irradiance. During photostress, pupil constriction ( C p ) was measured. Twenty-seven subjects (20–27 years) were exposed to white photostress. After 25 s of photostress, the time (PSRT) required to read correctly a 0.2 logMAR letter was measured. Correlation was studied between PSRT, C P, and irradiance. Statistical significance of differences between PSRTs was evaluated at Log(irradiance(quanta s −1 cm −2 )) = 14 by Student's t statistics. Results : C p and PSRT were found linearly correlated to Log(irradiance) for blue, green, and white. At Log(irradiance(quanta s −1 cm −2 )) = 14, blue and green mean PSRTs resulted different ( p < 0.001) with 3.8 ± 0.8 s and 6.7 ± 1.7 s, respectively. After correcting irradiance for the optical absorption of MP, mean blue PSRT became 6.6 ± 0.8 s, at the logarithm of MP-corrected irradiance in quanta s −1 cm −2 equal to 14 ( p = 0.571 compared to green PSRT). For white light, at the logarithm of MP-corrected irradiance in quanta s −1 cm −2 equal to 14, mean PSRT was 7.5 ± 2.2 s, not significantly different from blue and green PSRT ( p > 0.05). Conclusions : MP plays the role of an optical filter attenuating photostress. PSRT was substantially proportional to the number of incident photons corrected for the MP optical absorption, regardless of their wavelength.